ANALISIS PENGARUH PRODUKSI DAN KONSUMSI TERHADAP IMPOR SUSU SAPI DI INDONESIA TAHUN 2017-2021 - Diezly Virena Br Ginting; Fika Salsabila; Indah Maharani; M. Aqila Arzako; Nancy Ortega Sitanggang (Investama : Jurnal Ekonomi dan Bisnis, 2023)
The goal of this study was to analyze the effect of production and consumption of cow's milk on the number of imports of cow's milk in Indonesia. The method used in this study is a descriptive method and data analysis sourced from the 2022 Animal Husbandry Statistics and Animal Health book by the Directorate General of Animal Health Animal Husbandry, Ministry of Agriculture of the Republic of Indonesia and the official website of the Central Bureau of Statistics 2017-2021. Consumption of milk in Indonesia has increased by an average of 4,413,009 tons in five years due to increased demand. Meanwhile, domestic milk production is still low with an average of 943,390 tons in five years due to the stationary population of dairy cows in Indonesia. Thus, to meet the domestic demand for milk, it is imported. This shows that consumption and domestic production of Indonesian milk affect the amount of milk imports in Indonesia. Where, consumption has a positive and significant influence on milk imports compared to domestic milk production. Keywords: imports, production, consumption